The relationship between parental mental health, reflective functioning coparenting and social emotional development in 0-3 year old children - De Palma, Mia; Rooney, Rosanna; Izett, Elizabeth; Mancini, Vincent; Kane, Robert (Frontiers in Psychology, 2023)
Introduction The transition to parenthood is a high-risk period for many parents and is an important period for child development. Research has identified that parental mental health, reflective functioning (capacity to consider mental states of oneself and others) and coparenting (capacity to work together well as a parenting team) may be particularly significant predictors of later child outcomes, however these factors have seldom been considered together. The present study therefore aimed to investigate the relationship between these factors and the extent to which they predict child social emotional development. Methods Three hundred and fifty parents of infants aged 0 to 3 years 11 months were recruited to complete an online Qualtrics questionnaire. Results Results indicate that both positive coparenting and parental reflective functioning (Pre-mentalizing and Certainty subscales) were found to significantly predict child development. General reflective functioning (Uncertainty subscale) predicted parental depression and anxiety, however unexpectedly, parental mental health was not a significant predictor of child development, but did predict coparenting. General reflective functioning (Certainty subscale) was also found to predict coparenting, which in turn was found to predict parental reflective functioning. We found an indirect effect of general reflective functioning (Certainty) on child SE development via parental reflective functioning (Pre-mentalizing). We also found an indirect effect of negative coparenting on child development via parental reflective functioning (Pre-mentalizing). Discussion The current results support a growing body of research highlighting the important role reflective functioning plays in child development and wellbeing as well as parental mental health and the interparental relationship.